Moral, Media, dan Madrasah: Suara Remaja Muslim tentang Bahaya Pornografi di Dunia Digital - Minhah Uulaa; Marwah Nur Azizah; Khodijah; Ahmad Adnan (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
This study aims to understand the perceptions of madrasah students toward the phenomenon of pornography addiction. It seeks to analyze how adolescents, specifically students of MTs Negeri 1 Jakarta, define the issue of pornography, identify the actors perceived as the causes of the problem, provide moral evaluations, and propose recommendations for addressing pornography addiction. The informants in this study consist of seven students from MTs Negeri 1 Jakarta. Data were collected through interviews with these students, while data analysis was conducted using Robert M. Entman’s framing analysis, which includes four dimensions: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings indicate a high level of social and moral awareness regarding the issue of pornography addiction. The students view pornography as a deviant behavior resulting from weak self-control, lack of family supervision, and exposure to negative content on social media. They perceive pornography addiction as a moral deviation that damages one’s character, emotions, and social relationships, emphasizing the importance of collaborative solutions through moral education, counseling, and spiritual reinforcement. These findings suggest that Muslim adolescents in madrasahs have the potential to become digital moral agents if supported by media literacy and religious education that are relevant to the digital era.